Identifikasi Kandungan Senyawa Bioaktif Buah Kapulaga (Amomum compactum) - Tarigan, Andesmeta; Saragih, Horasdia (Jurnal Gizi, 2023)
Traditionally, cardamom seed has been widely used by the community as herbal medicine. Cardamom seed has been phenomenologically proven to cure several types of diseases. This property is determined by the type of compounds contained in cardamon seed. The purpose of this research isidentification of the types of bioactive compounds contained in cardamom seed. These bioactive compounds are extracted using solvents: ethanol, methanol and water. Then, these bioactive compounds were identified using gas chromatography-mass spectroscopy (GC-MS) technique. The results obtained indicated that there were 13 types of compounds produced from ethanol extract, 6 types of compounds from methanol extract, and 2 types of compounds from aqueous extracts. From all these compounds, 1,8-cineole and alpha-terpineol compounds are the two most dominantsequentially. Referring to these results and the literature search that has been done, cardamom seed is potential to be developed in the future as herbal medicine to treat diseases, such as: diarrhea, cardiovascular disease, digestive disease, Alzheimer's, tumors, inflammation, cancer, pneumonia, neurodegenerative and respiratory diseases.Keywords : Compound identification, extract, cardamom seed, cineole, terpineol.